A Case Report on Heart Failure in Dengue Patients with Concurrent Capillary Leakage Syndrome: Unveiling a “Leakage-Failure” Co-existence - Mohammad Abdul Motalib; Md Zulfikar Ali; Sagar Ahammed (KYAMC Journal, 2024)
This case report describes a rare and compelling presentation of Massive Tubercular Pericardial Effusion (MTPE) concomitant with Heart Failure (HF) and Diabetes Mellitus (DM). Tuberculosis, once thought to be a disease of the past, continues to manifest in diverse clinical scenarios, emphasizing the importance of maintaining a high index of suspicion, particularly in endemic regions. The patient, a 60 year old male with a known history of DM and HF, presented with symptoms of worsening dyspnea, fatigue, and peripheral edema. Diagnostic workup revealed a massive pericardial effusion with characteristics suggestive of tubercular etiology, subsequently confirmed by pericardial fluid analysis. The challenges in managing this triad of conditions: MTPE, HF, and DM were addressed through a multidisciplinary approach involving cardiology, infectious disease, and endocrinology specialists. This case underscores the significance of a comprehensive diagnostic evaluation and collaborative management in optimizing outcomes for patients with complex cardiovascular and infectious comorbidities. KYAMC Journal Volume: 14, No: 04, January 2024: 246-248.